2011
DOI: 10.1093/ajae/aaq123
|View full text |Cite
|
Sign up to set email alerts
|

Who Participates in Household Scanning Panels?

Abstract: We compare two widely used household scanning panels maintained by the Nielsen Company and Information Resources Inc. to a random sample of the U.S. population. Results indicate that the demographic characteristics of the random sample more closely match the Census Bureau data than the household scanning panels. We also show that after controlling for demographic differences, participants in the household scanning panels are slightly more price sensitive than participants in the random sample. The two househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 40 publications
(42 reference statements)
3
37
1
Order By: Relevance
“…For the household level analysis, it has been previously reported that the Homescan sample does not perfectly match the US population based on demographics, and that males and individuals with low education are underrepresented. 33 Ideally, the sample should represent the population of US food/beverage shoppers rather than the overall US population. Without knowledge of the true US food/beverage shopper population, generalizing the results from this sample of shoppers should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the household level analysis, it has been previously reported that the Homescan sample does not perfectly match the US population based on demographics, and that males and individuals with low education are underrepresented. 33 Ideally, the sample should represent the population of US food/beverage shoppers rather than the overall US population. Without knowledge of the true US food/beverage shopper population, generalizing the results from this sample of shoppers should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Without knowledge of the true US food/beverage shopper population, generalizing the results from this sample of shoppers should be made with caution. Finally, given that households volunteered to participate, there is always the possibility of participation bias; 33 therefore, when possible, it is important to compare the results of Homescan with other dietary surveys (e.g., NHANES).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our sample may not be generalizable to the US population because of potential selection bias or nonresponse related to participant burden (37). Because our sample of relatively high-income households is not nationally representative and the distribution of income across racial/ethnic groups does not match that of the US population, all models were adjusted for income; results were interpreted with caution as associations between purchases and race/ethnicity independent of income, which potentially might reflect differences in food preferences, time constraints, or cultural traditions.…”
Section: Figurementioning
confidence: 94%
“…This analysis used data from the 2000-2012 Nielsen Homescan Panel, a nationwide study of CPG food and beverage purchases by US households (35)(36)(37)(38). Household members are given barcode scanners and are instructed to scan the barcodes on all foods and beverages purchased from grocery, drug, mass-merchandise, supercenter, and convenience stores and supermarkets.…”
Section: Study Populationmentioning
confidence: 99%
“…A fascinating paper by Lusk and Brooks (2011) suggests that households in two large US scanner samples, Homescan and IRI, appear to be more price responsive than the population at large. They take random samples from the scanner surveys and from a random-digit-dialing survey of all households, and use webbased questionnaires to elicit a series of discrete choices over grocery products from which elasticity estimates are derived.…”
Section: Previous Researchmentioning
confidence: 99%